ANALISIS FAKTOR DETERMINASI MINAT BERWIRAUSAHA MAHASISWA - Nurfatwa Andriani Yasin; Afriyani Afriyani; Syahribulan Syahribulan (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2022)
This study aims to analyze the effect of income expectations on students' interest in entrepreneurship through entrepreneurship education, and analyze the influence of the family environment on students' interest in entrepreneurship through entrepreneurship education. The data analysis method used is path analysis using Partial Least Square (PLS). The object of research is 250 students of STIE Tri Dharma Nusantara majoring in management at the final level. The results showed that income expectations had a positive and significant effect on interest in entrepreneurship through entrepreneurship education, and the family environment had a positive and significant effect on interest in entrepreneurship through entrepreneurship education.